Letter from the Editor-in-Chief - Chicheł, Adam (Journal of Contemporary Brachytherapy, 2021)
It is my honor to introduce the last issue of the “Journal of Contemporary Brachytherapy” this year. The present year is heading to its’ end, and I hope it is the last one to be so tremendously impacted by the COVID-19 pandemic. Somehow, we got used to cope with all the restrictions influencing our cancer treatment efforts and patient care. We were able to get available vaccines, follow hygienic recommendations, and persuade the vaccination opponents to accelerate the process of eliminate this awful virus. I wish all to prosper ‘normally’ finally.